Legalitas Pelaksanaan Tugas Pengamanan Oleh Pacalang Dalam Sistem Keamanan Nasional - Firmantara, I Kadek Agus Aditya; Yanti, A.A. Istri Eka Krisna (Kertha Patrika; Vol 46 No 2 (2024)DO - 10.24843/KP.2024.v46.i02.p05, 2024)
This study aims to examine the legality of the security duties carried out by Pecalang within Indonesia's national security system. As a state based on law, Indonesia recognizes and respects the traditional rights of customary law communities, including those in Bali. Pecalang, a traditional security task force in Balinese customary villages, plays a crucial role in maintaining order and security. The research method employed is normative legal research with a documentary approach to relevant legal products. The analysis focuses on the legal basis of Pecalang's authority, their position within the national security system, and the regulations governing their role. The findings indicate that Pecalang have a solid legal foundation based on Regional Regulation No. 4 of 2019 concerning Customary Villages, which regulates their role in maintaining order within the Customary Village. Additionally, Pecalang are recognized in Law No. 2 of 2002 concerning the National Police of the Republic of Indonesia as part of self-initiated security, whose role is to support the police in maintaining security. Pecalang perform their duties based on awig-awig (customary regulations) created by the customary village, providing a legal basis for them to carry out security and order functions according to customary law. However, challenges include negative public perceptions and actions that exceed their official authority. Therefore, there is a need for increased socialization and education for the community regarding the role of Pecalang, as well as an increase in the number of Pecalang within the community.